2015
DOI: 10.1007/978-3-319-23660-5_10
|View full text |Cite
|
Sign up to set email alerts
|

The Degree of Squares is an Atom

Abstract: We answer an open question in the theory of degrees of infinite sequences with respect to transducibility by finite-state transducers. An initial study of this partial order of degrees was carried out in [5], but many basic questions remain unanswered. One of the central questions concerns the existence of atom degrees, other than the degree of the 'identity sequence' 10 0 10 1 10 2 10 3 • • •. A degree is called an 'atom' if below it there is only the bottom degree 0, which consists of the ultimately periodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 8 publications
(9 reference statements)
0
30
0
Order By: Relevance
“…A key notion of [3,2] is the pre-order ≥ defined on sequences by σ ≥ τ ⇐⇒ ∃ finite state transducer T : τ = T (σ ).…”
Section: One-sided Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A key notion of [3,2] is the pre-order ≥ defined on sequences by σ ≥ τ ⇐⇒ ∃ finite state transducer T : τ = T (σ ).…”
Section: One-sided Sequencesmentioning
confidence: 99%
“…Equivalence under transducers organizes infinite sequences into a hierarchy with interesting properties, as ongoing research is revealing, see for example [2,4]. Under the stricter notion of equivalence under permutation transducers a finer hierarchy of one-sided sequences arises, as well as a novel hierarchy of bi-infinite sequences (in fact, two distinct versions of them, see below).…”
Section: Introductionmentioning
confidence: 99%
“…We use ≥, ∼, > for the similar relations on sequences based on ordinary finite state transducers, that is, without the additional bijectivity requirement. These were studied extensively in [3][4][5][6]. To see the effect of the additional requirement of permutation transducers, throughout the paper in presenting properties of ≥ p , ∼ p , > p we often present the corresponding properties of ≥, ∼, >.…”
Section: Definition 1 a Finite State Transducermentioning
confidence: 99%
“…A main result of [4] states that the class containing the sequences of the shape f for f linear is atomic, that is, if f ≥ σ for f linear, then either σ ≥ f or σ is ultimately periodic. In [3] it was shown that a similar result holds for quadratic functions, while in [5,6] it was shown that for higher degree it does not hold. Here we are interested in considering ≥ p and ∼ p instead.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation